2018
DOI: 10.1002/srin.201800050
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer Characteristic during Inclination Circular Jet Impingement on the Hot Plate Surface

Abstract: The heat transfer process of the inclination round jet impingement is studied experimentally for improving the cooling capacity and uniformity of the ultrafast cooling used in Thermo-mechanical Control Process. The heat transfer characteristic is presented for jet inclination angle from 0 to 60 . The video images of heat transfer process and heat flux curves demonstrate that the wetted region extends asynchronously due to the uneven water flow distribution. In the forward flow direction, the larger parallel fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 26 publications
4
11
2
Order By: Relevance
“…This indicates that downhill flow direction exhibits higher cooling ability and cooling uniformity compared with the uphill flow direction. Similar observations have been made by Wang et al during their investigation.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…This indicates that downhill flow direction exhibits higher cooling ability and cooling uniformity compared with the uphill flow direction. Similar observations have been made by Wang et al during their investigation.…”
Section: Resultssupporting
confidence: 92%
“…The comparison of maximum surface heat flux obtained from the present study with the results of Xie et al and Wang et al is shown in Figure . Studies have been made to estimate the maximum heat flux during the cooling of hot horizontal plates for various jet inclination angles ( θ =90°–15°) . Xie et al performed tests with top jet water impingement on 20 mm thick steel plate (AISI 314) for a varied range of jet inclination angles ( θ = 90°–30°).…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations